New insights into interpreting studies. Technology, society and access - Book review - Pelea, Alina (English Studies at NBU, 2025)
Book Details Title: New Insights into Interpreting Studies. Technology, Society and Access Volume Editors: Agnieszka Biernacka, Wojciech Figiel Publisher: Peter Lang, 304 pages Year of publication: 2024 ISBN: 9783631884850 (hardcover), 9783631907139 (ePub), 9783631907122 (PDF)